Communication at Microsoft Services Asia (B) - ANG, Jovina (Institutional Knowledge at Singapore Management University, 2012)
Case B follows Case A where Cassandra Lee, the director of marketing communications of Microsoft Services Asia was tasked to develop a plan to address employee morale and engagement. In this case the primary issue centres on how a leader can take an organisation to the next level by setting a big, bold and aspirational goal. This case encourages discussion not only on the importance of clearly communicating the goal to every employee, but also that strategies and initiatives have to be put in place to focus employees to shoot collectively for a common and significant goal.